Immunomodulatory activity of glycoproteins isolated from chickpea (Cicer arietinum L.) - Shi, Zhenxing; Li, Shiyu; Wei, Zuchen; Wang, Yuanji; Zhou, Nong; Ma, Qiang; Yao, Yang (Frontiers in Nutrition, 2022)
Chickpea (Cicer arietinum L.) is a well-known legume widely used as traditional medicine. This study aimed to characterize the structure and evaluate the immunomodulatory activity of one glycoprotein [crude chickpea glycoprotein-1 (CAG-1)] isolated from chickpea. CAG-1 was extracted with hot alkaline water and purified with DEAE-Sepharose Fast Flow and Superdex-200 column chromatography. CAG-1, with a molecular weight of 8,106 Da, contained 57.12% polysaccharide and 35.41% protein. The polysaccharide part was mainly composed of glucose (Glc). The protein part was connected mainly by aspartic (Asp) and glutamic (Glu). The results of nuclear magnetic resonance (NMR) analysis indicated the presence of α-d-Glcp-(1 → 4)-α-d-Glcp-(1 → 4)-α-d-Glcp-(1 → . In addition, the sugar chains of the glycoprotein were not hydrolyzed under alkaline conditions, suggesting that the glycoprotein was N-glycosidic; thus, the sugar chain was linked to the protein chain by Asp. An immunological study showed that CAG-1 stimulated the production of nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and monocyte chemotactic protein 1 (MCP-1) in RAW 264.7 macrophages in a dose-dependent manner.